Cytotoxic and Antiproliferation Activity of n-Hexane Fraction of Avocado seed (Persea americana Mill.) on MCF7 cell - Juwita Rahwawati; Maryati Maryati; Ratna Yuliani (Pharmacon: Jurnal Farmasi Indonesia, 2022)
Avocado seeds, which often end up as food waste, have many health benefits, including anticancer activity. This study aimed to determine the potential cytotoxic activity of avocado seeds against breast cancer cells, MCF7. Avocado seeds were macerated with 96% ethanol and fractionated with n-hexane, chloroform, and ethyl acetate as solvents. Cytotoxic activity of the extract and fractions was tested using the MTT method, while antiproliferation activity and apoptosis of the n-hexane fraction were tested using the doubling time and double staining methods, respectively. The selectivity of the n-hexane fraction was also determined. The results showed that the extract and n-hexane fraction of avocado seeds had cytotoxic activity on MCF7 with IC50 values of 211.2±25 and 47.87±1.5 µg/mL, respectively. The cytotoxic activity of the n-hexane fraction was selective (Selectivity Index = 4.73). The fraction can extend the doubling time to 76.54-77.41 hours. The double staining test results showed red fluorescence in the cells, indicating the apoptosis of MCF7 cells. The n-hexane fraction of avocado seed extract has the potential to be developed as an anticancer therapeutic agent.